Lethal yellowing disease of coconut palms - Mccoy, R. E.; Norris, R. C.; Vieyra, G.; Delgado, S.
The confirmation of this disease in Mexico in Jan. 1982 is also the first report of its presence in a coconut-growing area of mainland Central America. Sieve tube elements of the phloem from affected palms contained mycoplasma-like organisms. In Cancún approx. 20 percent of the coconut palms died in one year, most having symptoms of lethal yellowing. This outbreak poses a serious threat to commercial coconut production in the Yucatan Peninsula.
Keywords: COCOS NUCIFERA; MYCOPLASMATACEAE; COCONUTS; DISEASES; FATTY OIL PLANTS; GEOGRAPHY; LETHAL YELLOWING; OIL PLANTS; OILSEED PLANTS; PLANT PATHOLOGY